The association between the socioeconomic status and anxiety–depression comorbidity in patients with psoriasis: a nationwide population‐based study. (6th June 2019) - Tzur Bitan, D.; Krieger, I.; Comaneshter, D.; Cohen, A.D.; Feingold, D.
Abstract: Background: Numerous studies have indicated that comorbid anxiety and depression are associated with a more severe course of illness. Yet generally, the study of the effect of psoriasis on patients' mental health has considered anxiety and depression to be separate states. Objective: To measure the association between psoriasis and anxiety, depression and anxiety–depression co‐occurrence among patients according to their socioeconomic statuses (SES). Methods: A nationwide population‐based study of psoriasis patients and age and gender frequency‐matched controls ( n  = 255 862) was designed. Diagnostic data were obtained from Clalit Health Services, the largest managed care organization in Israel. This database was established using continuous real‐time input from healthcare providers, pharmacies, medical care facilities and administrative computerized operating systems. Results: After controlling for demographic and clinical variables, psoriasis was associated with anxiety (OR 1.11, 95% CI 1.01–1.23, P  < 0.05), depression (OR 1.17, 95% CI 1.08–1.26, P  < 0.001), and anxiety and depression co‐occurrence (OR 1.32, 95% CI 1.21–1.45, P  < 0.001) among patients with low SES, yet was associated only with anxiety (OR 1.15 95% CI 1.04–1.27, P  < 0.001) but not depression or comorbid anxiety–depression among patients with high SES. Survival analyses indicated that between the ages of 40 and 60, the cumulative probability of psoriasis patients with low SES to suffer from anxiety, depression and their co‐occurrence inclined more sharply with age as compared to psoriasis patients with high SES. Conclusions: As psoriasis patients with low SES are prone to suffer from more severe courses of anxiety and depression, the choice of treatment of psoriasis should address the SES as well as the underlying psychiatric disease.